Forecasting of Crossbred Pig Price with Box-Jenkins method - สิทธิสร, ภัฐชญา; เมฆพายัพ, จตุภัทร (Progress in Applied Science and Technology, 2017)
The aim of this research was to forecast crossbred pig price using monthly crossbred pig price, price of pig weight at least 100 kilograms. For fitting model, data was used since January 2006 to December 2016 (132 cases). For efficient validation, data was used from January to May in 2017 (5 cases). The results found that there were two forecasting models of Box-Jenkins; model and model, both were models without constant. The most appropriate model for forecasting crossbred pig price was model with no constant with root mean squared error, mean absolute error, mean absolute percentage error, normalized mean square error and factor of two equal to 2.1448, 1.6391, 2.8398, 0.0013 and 1 respectively.